2010
DOI: 10.1124/jpet.110.175620
|View full text |Cite
|
Sign up to set email alerts
|

The First Universal Opioid Ligand, (2S)-2-[(5R,6R,7R,14S)-N-cyclopropylmethyl-4,5-epoxy-6,14-ethano-3-hydroxy-6-methoxymorphinan-7-yl]-3,3-dimethylpentan-2-ol (BU08028): Characterization of the In Vitro Profile and In Vivo Behavioral Effects in Mouse Models of Acute Pain and Cocaine-Induced Reward

Abstract: Certain behavioral features of buprenorphine, including a bellshaped curve for antinociception and attenuation of alcohol consumption, are thought to be mediated by activation of nociceptin/orphanin FQ peptide (NOP) receptors, despite moderate affinity and low efficacy at NOP receptors. We hypothesized that ligands with buprenorphine's physical properties, but possessing increased NOP receptor affinity and efficacy, would improve the profile as a drug abuse medication and reduce addiction liability. Using this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 36 publications
3
71
2
1
Order By: Relevance
“…More interestingly, antagonist studies have demonstrated that both MOP and NOP receptors contribute to BU08028-induced antinociception in primates. This is in contrast to rodent studies showing that pretreatment with a NOP receptor antagonist potentiated BU08028-induced antinociception (38). Nonetheless, the functional profile of BU08028 in monkeys provides proof of concept that a single molecule with mixed MOP and NOP agonist activity is more potent than selective ligands and devoid of MOP receptor-mediated side effects (17,25).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…More interestingly, antagonist studies have demonstrated that both MOP and NOP receptors contribute to BU08028-induced antinociception in primates. This is in contrast to rodent studies showing that pretreatment with a NOP receptor antagonist potentiated BU08028-induced antinociception (38). Nonetheless, the functional profile of BU08028 in monkeys provides proof of concept that a single molecule with mixed MOP and NOP agonist activity is more potent than selective ligands and devoid of MOP receptor-mediated side effects (17,25).…”
Section: Discussioncontrasting
confidence: 51%
“…The high logP value of BU08028 could contribute to its unique pharmacokinetic profile (30,38). More interestingly, antagonist studies have demonstrated that both MOP and NOP receptors contribute to BU08028-induced antinociception in primates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is the first to demonstrate antihypersensitive effects of intrathecally administered bifunctional NOP/MOP ligands in neuropathic and inflammatory pain. Intrathecal BU08028 and SR16435, both of which bind to NOP and MOP with high affinity (K i 5 2-8 nM) and partial efficacy as measured by guanosine 59-O-(3-[ 35 S]thio)triphosphate functional assay (20-50% stimulation) (Khroyan et al, 2007(Khroyan et al, , 2011a, were more potent than intrathecal SCH221510 or morphine for their antihypersensitive effects (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we studied bifunctional ligands with high affinity and partial agonist activity at NOP and MOP-BU08028 [2-(N-cyclopropylmethyl-4,5-epoxy-6,14-ethano-3-hydroxy-6-methoxymorphinan-7-yl)-3,3-dimethylpentan-2-ol] and SR16435 [1-(1-(2,3,3a,4,5, 6-hexahydro-1H-phenalen-1-yl)piperidin-4-yl)-indolin-2-one]-but without agonist activity at d-and k-opioid receptors (Khroyan et al, 2007(Khroyan et al, , 2011a, and we compared them with the selective NOP and MOP agonists as well as buprenorphine. In addition, we compared potential tolerance development to the antiallodynic effects of SR16435 and buprenorphine, which have similar duration of actions, after repeated intrathecal administration.…”
Section: Introductionmentioning
confidence: 99%